2002
DOI: 10.1016/s0893-133x(02)00314-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Risperidone on the Peripheral Noradrenegic System in Patients with Schizophrenia A Comparison with Clozapine and Placebo

Abstract: Risperidone is an atypical antipsychotic drug that increases plasma norepinephrine (NE) levels, but the mechanism behind this effect is unclear. We measured arterial plasma levels of NE and other catechols during intravenous infusion of tritium-labeled NE ( 3 H-NE) in risperidone-Clozapine is an atypical antipsychotic drug (APD) with efficacy superior to that of conventional agents and with little or no extrapyramidal signs or symptoms (EPS) (Kane et al. 1988;Lieberman et al. 1989;Breier et al. 1994a;Meltzer 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 59 publications
0
16
0
1
Order By: Relevance
“…Briefly, mRNA of the DA receptors peaked at week 2 after taking antipsychotics, after which it decreased but was above baseline at week 8 [76,77] . Finally, it has been reported that both risperidone and clozapine elevate plasma NE levels, with risperidone producing a smaller effect [85] . Logically, considering their close ties with the pharmacological properties of antipsychotics, peripheral monoamine related molecules might be a good indicator for treatment response but current evidence to support this posit is lacking.…”
Section: Monoamine Pathwaysmentioning
confidence: 96%
“…Briefly, mRNA of the DA receptors peaked at week 2 after taking antipsychotics, after which it decreased but was above baseline at week 8 [76,77] . Finally, it has been reported that both risperidone and clozapine elevate plasma NE levels, with risperidone producing a smaller effect [85] . Logically, considering their close ties with the pharmacological properties of antipsychotics, peripheral monoamine related molecules might be a good indicator for treatment response but current evidence to support this posit is lacking.…”
Section: Monoamine Pathwaysmentioning
confidence: 96%
“…Likewise, potential contributions to weight gain of norepinephrine (Elman et al, 2002(Elman et al, , 2004 and prolactin (Melkersson, 2005;Mann et al, 2006) increases associated with SGA treatment are still unclear. The findings of SGA effects on the brain BDNF (Bai et al, 2003;Luo et al, 2004;Angelucci et al, 2005) and orexin in preclinical literature may be also of potential importance as both neurochemicals are involved in reward and appetitive functions; however, their precise role and how they are influenced by SGAs in humans (Dalal et al, 2003;Weickert et al, 2005) are intriguing topics for future research.…”
Section: Putative Mechanisms Of Sgas-induced Weight Gainmentioning
confidence: 99%
“…18 -20 Similarly, a desensitization of NET after a 14-day treatment with the tricyclic drug desipramine has been suggested on the basis of in vivo electrophysiological results obtained in the rat hippocampus. 21 Whether ␣ 2 -adrenergic autoreceptors, which negatively control the release of NE, desensitize after long-term antidepressant 22 Moreover, the reduction in plasma DHPG by NET blockade probably reflects both reduced central sympathetic outflow (yielding less peripheral NE synthesis) as well as peripheral NET blockade.…”
Section: Vincent Et Al Norepinephrine Transporter and Pharmacodynamicsmentioning
confidence: 99%